2017
DOI: 10.15850/amj.v4n2.1094
|View full text |Cite
|
Sign up to set email alerts
|

Two Years Profile of Anemia in Systemic Lupus Erythematosus Patients at West Java’s Top Referral Hospital, Indonesia

Abstract: Background: Anemia is a common clinical manifestation in Systemic Lupus Erythematosus (SLE) patients. Anemia can be caused by an ineffective hematopoietic process or excessive red blood cell destruction. The aim of this study was to classify and characterize anemia in SLE patients. Methods: This study involved 97 outpatients visiting the Rheumatology Clinic of Dr. Hasan Sadikin General Hospital Bandung, from January 2013 to September 2014. Patient data was collected from medical records and study subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…According to morphology, normochromic normocytic anemia in 61 patients (57.55%) was the most frequent hematological manifestation of anemia which is strongly connected to anemia of chronic disease [22]. Similar results by Rouf et al, Usman et al, and Uskudar Teke et al also found SLE patients with normochromic normocytic anemia in most of the sample [7][22] [23] .…”
Section: Resultssupporting
confidence: 66%
“…According to morphology, normochromic normocytic anemia in 61 patients (57.55%) was the most frequent hematological manifestation of anemia which is strongly connected to anemia of chronic disease [22]. Similar results by Rouf et al, Usman et al, and Uskudar Teke et al also found SLE patients with normochromic normocytic anemia in most of the sample [7][22] [23] .…”
Section: Resultssupporting
confidence: 66%